AB0904 Pericarditis as A Possible Predictor for Biological Disease Modifying Anti-Rheumatic Drugs Need in Adult Onset Still's Disease. (15th July 2016) - Dall'ara, F.; Frassi, M.; Tincani, A.; Airò, P.
Abstract : Background: Adult onset Still's disease (AOSD) is a rare systemic inflammatory disorder of unknown aetiology, which is considered to be similar to systemic-onset juvenile idiopathic arthritis (SOJIA). Peculiar clinical and laboratory features of SOJIA and AOSD led some authors to propose that these diseases should be included among the family of autoinflammatory diseases related to abnormalities in innate immune system. The optimal treatment strategy of AOSD is difficult to determine because of the absence of large-scale prospective studies. Predictive factors of outcome would be useful to draw guidelines for patient management. Objectives: To look for clinical or serological markers able to predict the use of biological disease modifying anti-rheumatic drugs (bDMARDs) in patients with AOSD. To evaluate the efficacy and safety of bDMARDs in AOSD. Methods: In a single-center retrospective study, 42 patients with AOSD were divided into two groups according to whether they were ever treated with bDMARDs (n:20) or not (n:22). Literature was searched for articles dealing with possible predictors of the use of bDMARDs in AOSD. Results: Among 20 AOSD patients who received at least one bDMARDs, the prevalence of pericarditis was higher than in the other patients (8/20 vs 1/22; p:0.008; OR, 14.0, 95% CI 1.56 to 126). Literature search retrieved another paper dealing with predictors of bDMARDs need in AOSD (1): the analysis pooling data from our series and literature confirmed pericarditis at disease onset as a predictor of bDMARDs need (p:0.018; OR, 3.81, 95% CI 1.31 to 11.1). A complete remission was observed in 17 out of 18 evaluable patients treated with bDMARDs, allowing withdrawal or tapering of corticosteroid therapy (p<0.001), but, because of inefficacy or adverse events, some patients received more than one bDMARD during the course of the disease, and 33 different trials of bDMARDs were needed. Conclusions: Pericarditis is a possible marker of the auto-inflammatory process that may underlie the pathogenesis of AOSD. Pericarditis at disease onset may be a predictor of bDMARDs need. Biological DMARDs have a good efficacy and safety profile in AOSD, and should be considered for patients not responding to conventional therapy. References: Quartuccio L, et al. Clin Exp Rheumatol 2012;30:807. Disclosure of Interest: None declared